El Enfoque del Marco Logico /NORAD - NORAD (España:NORAD, 1992)
Trata de los conceptos y aplicaciones de la Metodología de Marco Lógico.
1.Participacion 2.Problema
incluye índice
Col.Met.Inv
Keywords: 1.DISEÑO DE PROYECTO 2.EML 3.DEFINICIONES